2021
DOI: 10.1080/20477724.2021.1893485
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features and outcomes of hospitalized COVID-19 patients in a low burden region

Abstract: Data on the clinical features and outcomes of COVID-19 patients from countries with low disease burden are rare. Greece, however, presented a low burden of COVID-19 disease during the rst pandemic outbreak. This is a retrospective study of COVID-19 hospitalized patients in Greece. Clinical data were extracted from medical records using univariable and multivariable logistic regression analysis to assess the factors associated with ICU admission and in-hospital death. Eighty ve patients were included in this st… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…A large number of studies have shown that comorbidities, [6][7][8][9][10][11][12] such as hypertension, diabetes, cardiovascular disease, hepatic, pulmonary disease, etc can increase the risk of COVID-19 mortality. Could COVID-19 patients also have an increased risk of death after suffering from human immunodeficiency virus (HIV) co-infection?…”
Section: Introductionmentioning
confidence: 99%
“…A large number of studies have shown that comorbidities, [6][7][8][9][10][11][12] such as hypertension, diabetes, cardiovascular disease, hepatic, pulmonary disease, etc can increase the risk of COVID-19 mortality. Could COVID-19 patients also have an increased risk of death after suffering from human immunodeficiency virus (HIV) co-infection?…”
Section: Introductionmentioning
confidence: 99%
“…However, these estimates could be affected by methodological limitations, including small sample sizes. [10][11][12]29 Our study cannot estimate mortality rates for that period, as there were hardly any hospitalized cases in Crete, in accordance with a very low epidemiological burden. However, we report overall comparably higher mortality rates than the studies mentioned above with most of our cases and deaths occurring in the last quarter of 2020 and for the first third of 2021.…”
Section: Time Period Case Load and In-hospital Mortalitymentioning
confidence: 75%
“…In Greece, most of the published observational studies report data from the spring of 2020 (the "first wave" of the pandemic), when the epidemiological burden of Greece was especially low and report also low in-hospital mortality rates. [10][11][12] A study on a sample of 50 intensive care unit (ICU) patients in Athens in the spring of 2020 suggested hospital resources as an important factor to explain differences in internationally reported in-hospital case fatality rates. 13 Additionally, case load (even when capacity is not exceeded) and regional disparities seemed to also influence mortality rates of the critically ill. 14 However, it has proven challenging to assess the relative contribution of the former factors in the measured case fatality rates, which are characterized from extreme heterogeneity.…”
Section: Introductionmentioning
confidence: 99%
“…The Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) pandemic has resulted in more than 3 million deaths worldwide [1], suggesting the need of more efforts in Public Health [2]. Major risk factors for Coronavirus Disease 2019 (COVID-19) adverse outcomes and mortality include preexisting chronic diseases (eg, diabetes, hypertension, obesity, and kidney diseases), as well as Human Immunodeficiency virus (HIV) infection [3][4][5]. Indeed, several findings suggest that the risk of COVID-19 mortality is more than two time higher among people living with HIV (PLHIV) than those HIV-seronegative [6-9].…”
Section: Discussionmentioning
confidence: 99%